Diskursus dan Otoritas dalam Penggunaan Isra’iliyyat - Muhammad Ulil Albab Aziz; Muhammad Haidar Syauqi Adnan (SUHUF, 2026)
This article examines the construction of discursive authority in addressing isra’iliyyat through a comparative analysis of the interpretation of surah Al-A‘raf (7): 157 in Ibn Kasir’s Tafsir Al-Qur’an al-‘Azim and Al-Qur’an dan Tafsirnya by the Ministry of Religious Affairs of the Republic of Indonesia. Employing Norman Fairclough’s Critical Discourse Analysis, this study critiques classical conceptions of exegetical authority that rely primarily on sanad-based transmission. The findings reveal that Ibn Kasir constructs authority through a rigorous tafsir bil-ma’sur methodology by filtering isra’iliyyat according to their conformity with the Qur’an, hadith, and the reliability of the chain of transmission. In contrast, the Ministry’s tafsir establishes authority through a tahliliy ijtima’iy approach that contextualizes Qur’anic meaning within Indonesia’s social realities and Pancasila values. Thus, exegetical authority is understood as a dynamic construction shaped by the interaction of scholarly principles, socio-historical contexts, and ideological interests.